The determination of copper in biological materials by flame spectrophotometry - Newman, G. E. (1962)
A method for the determination of the copper content of biological materials by flame spectrophotometry is described. The effects of interference by ions such as sodium and phosphate were eliminated by isolating copper as the dithizonate in CCl(4). Results obtained for the urinary excretion of copper by a patient with Wilson's disease before and after treatment with penicillamine are reported.